Pengaruh Kecerdasan Emosional terhadap Burnout pada Bidan di Ruang Covid RSUD SK Lerik tahun 2022 - Sumiyum Nardo; Lia Idealistiana (Universitas Aisyah Pringsewu (UAP) Lampung, 2022)
Burnout syndrome has been studied extensively as a three-dimensional syndrome involving emotional exhaustion (EE), cynical treatment and negative thoughts towards patients and health care teams (or depersonalization, DP), and low levels of personal achievement (PA) regarding the work performed by a person. individual. Burnout can be experienced by various professions, one of which is Midwife. Emotional intelligence means using emotions effectively to achieve a goal, build productive relationships to achieve success at work. Emotional intelligence is the bridge between what individuals know and do.